Al-Ghazali's Thought About Sufistic Education Character in The Book Minhajul Abidin - Wafa, Ali (Journal of Islam and Science, 2021)
Education character has become an important issue in the world of education lately, with the increasing and varied phenomena of moral decadence occurring in society and in government circles, especially among students. The government pays less attention to fostering education character. The government is more focused on continuous curriculum reform. This condition will get worse if the government, parents and schools or madrasah receive less serious attention. Sufistic education character is an important approach to be applied to overcome these moral decadency phenomena. Therefore, this study aims to provide alternative solutions in realizing children's education character both in the family environment, school environment and social environment. In addition, in this study the author offers several concepts of education character with the Sufistic character of al-Ghazali as in the book of Mohajul Abidin: first, preserving the eyes. Second, maintain the ears. Third, take care of the mouth. Fourth, maintain the stomach.Keywords: Biography of Al-Ghazali, Sufistic Education character in the book Minhajul Abidin